2013
DOI: 10.1111/ahg.12034
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Variation in Plasma Angiotensin‐I Converting Enzyme Activity Shows Allelic Heterogeneity in the ABO Blood Group Locus

Abstract: SummaryAngiotensin-I converting enzyme (ACE) occupies a pivotal role in cardiovascular homeostasis. Major loci for plasma ACE have been identified at ACE on Chromosome 17 and at ABO on Chromosome 9. We sought to characterise the genetic architecture of plasma ACE at finer resolution in two populations. We carried out a GWAS in 1810 individuals of Japanese ethnicity; this identified signals at ACE and ABO that together accounted for nearly half of the population variability of the trait. We conducted measured h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 29 publications
2
20
0
Order By: Relevance
“…This could explain why Ndel1 enzyme levels appear to a more complex trait than, for example, angiotensin I converting enzyme (ACE), other oligopeptidase that share common peptide substrates with Ndel1 (Terao et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…This could explain why Ndel1 enzyme levels appear to a more complex trait than, for example, angiotensin I converting enzyme (ACE), other oligopeptidase that share common peptide substrates with Ndel1 (Terao et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…This community-based prospective multiomics cohort study has been described in detail previously. 22,23 This cohort was recruited from the general population living in Nagahama City, a large rural city of 125,000 inhabitants in the Shiga Prefecture, located in the center of Japan. All participants voluntarily joined the study, which resulted in the difference in the number of participants of each sex.…”
Section: Study Populationsmentioning
confidence: 99%
“…This was confirmed in several meta-analyses (Narain et al, 2000; Kehoe et al, 2003; Elkins et al, 2004; Lehmann et al, 2005) and was supported to some extent by some of the earlier whole-genome association studies (Li et al, 2008; Thornton-Wells et al, 2008) although a number of more recent and larger studies have failed to find any association. In the original studies, homozygosity of the D and I alleles was associated with the highest and lowest ACE protein level in the periphery, respectively, (Rigat et al, 1990) although this association only partly explains the total variance of ACE in the periphery (Terao et al, 2013). We found that the ACE II genotype was associated with reduced ACE protein level in the CSF (Miners et al, 2010b).…”
Section: The Renin-angiotensin System In Alzheimer's Diseasementioning
confidence: 99%